2001
DOI: 10.1073/pnas.171283198
|View full text |Cite
|
Sign up to set email alerts
|

Apaf-1 deficiency and neural tube closure defects are found in fog mice

Abstract: The forebrain overgrowth mutation ( fog) was originally described as a spontaneous autosomal recessive mutation mapping to mouse chromosome 10 that produces forebrain defects, facial defects, and spina bifida. Although the fog mutant has been characterized and available to investigators for several years, the underlying mutation causing the pathology has not been known. Because of its phenotypic resemblance to apoptotic protease activating factor-1 (Apaf-1) knockout mice, we have investigated the possibility t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
61
0
1

Year Published

2003
2003
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 79 publications
(62 citation statements)
references
References 16 publications
0
61
0
1
Order By: Relevance
“…3,4 Apaf1 involvement in brain-mass control in a dosage-dependent manner was also confirmed by the analysis of the hypomorphic mutant fog (forebrain overgrowth), in which Apaf1 levels are strongly reduced. 27 We wondered whether Apaf1 is involved in the main route of NPCs to death, as suggested by the knockout mouse phenotype, and whether the path to death could be somehow prevented or reverted in Apaf1 À/À cells. Additionally, we wanted to know what was the quality of surviving Apaf1 À/À cells committed to die, and whether they retained their potential to differentiate.…”
Section: Discussionmentioning
confidence: 99%
“…3,4 Apaf1 involvement in brain-mass control in a dosage-dependent manner was also confirmed by the analysis of the hypomorphic mutant fog (forebrain overgrowth), in which Apaf1 levels are strongly reduced. 27 We wondered whether Apaf1 is involved in the main route of NPCs to death, as suggested by the knockout mouse phenotype, and whether the path to death could be somehow prevented or reverted in Apaf1 À/À cells. Additionally, we wanted to know what was the quality of surviving Apaf1 À/À cells committed to die, and whether they retained their potential to differentiate.…”
Section: Discussionmentioning
confidence: 99%
“…The apoptosome, although originally believed to be essential for Bcl-2-regulated apoptosis 171,172 , has more recently been defined as merely an amplifier of caspase activation. This was determined through studies which showed that in the absence of APAF1, or pro-caspase 9, cells could still die through Bcl-2 family driven apoptosis in lymphocytes and post mitotic neurones 173,174 . The apoptosome therefore appears to have more impact on apoptosis occurring in some cell types, such as lymphocytes, than in others, for example neuronal precursors 173 .…”
mentioning
confidence: 99%
“…Moreover, our allele phenocopies previously characterized Apaf1 deletion alleles that exhibit defects in neural tube closure, delayed interdigital web removal, embryonic lethality and craniofacial malformations. [18][19][20][21][22] Our data suggest that Shh-producing cells persist and direct a lateral outgrowth of the FNP that results in the craniofacial defects we observe. Because Apaf1 yautja encodes a stable, non-functional protein, this allele provides a valuable tool for examining apoptosome formation and activation.…”
Section: Discussionmentioning
confidence: 53%
“…The Apaf1 fog allele is functionally deficient in Apaf1 protein due to aberrant transcript processing. [21][22] Embryos heteroallelic for the yautja and fog alleles failed to complement and recapitulated features of both phenotypes: we saw defects of the forebrain, lumbosacral and facial regions, including forebrain encephalocele, exencephaly, open fourth ventricle, compressed forebrain ventricles, spina bifida with or without a kinked tail and wide or split face ( Figure 2d). We saw these features either in isolation or in complex, consistent with the individual mutant phenotypes for yautja and fog.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation